Cleft lip/ palate and its relationship with socio-demographic factors in 0-15 years old children attending tertiary care centre, Nandyal, Andhra Pradesh, India - G, Vijaya Vishnu; Pasha, M. A. M.; Fathima, Afsar; Gopichand, Sumana (International Journal Of Community Medicine And Public Health, 2017)
Background: Cleft lip with or without (CL) cleft palate and cleft palate alone (CP) are a major public health problem. It is a common developmental and serious birth defects associated with genetic and or environmental factors affecting 1 in every 500 to 1000 births worldwide. Methods: Objectives is to know the prevalence of cleft lip/ palate in children attending Santhiram medical college – Nandyal. Study design is cross sectional study with study population 137 children. Study was conducted for a period of one year from August 2015 –July 2016. Each respondent were interviewed with pretested and semi structured questioner. The limitation of this study was the sample size. We also need to maintain an accurate database for cleft registrations; systematic record keeping is essential in this area. Results: 70% of children were in age group of 0-5 years, 13.3% belongs to 6-10 years age group and 16.7% belongs to 11-15 yrs. 64.2% are Boys and 35.8% are girls were effected. 2.1% of uncles and grandparents have similar complaints. 7.4% of parents and 3.7% of siblings has similar complaints. 33.3% has risk factor consanguineous marriage. Conclusions: Boys were more effected than girl children. 2.1% of uncle’s and grandparents has similar complaints. 7.4% of parents and 3.7% of siblings has similar complaints. Majority has risk factor as consanguineous marriage, followed by history of OCP intake, smoking in family, obesity of mother as risk factor and other siblings with similar complaints. Majority has defect on left side.